PERAN BAITUL MAL SEBAGAI PENGHIM PERAN BAITUL MAL SEBAGAI PENGHIMPUN DANA ZAKAT DALAM MENANGGULANGI KEMISKINAN DI KOTA LANGSA - mulyadi mulyadi (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2021)
Aceh is one of the provinces with a high poverty rate and is also a region with a high poverty rate in Sumatra, including Langsa City. Therefore, one of the efforts to alleviate poverty in Langsa City is by utilizing zakat funds managed by the Baitul Mal Institute, which will later be distributed to the poor in Langsa City. This study aims to identify the role of the Baitul Mal Institution in alleviating poverty and improving the welfare of the people of Langsa City. From the research results, it is concluded that the distribution of zakat funds to the poor is still ineffective and still not on target so that people still do not feel prosperity.